Soluble programmed cell death receptor-1 (sPD-1): a potential biomarker with anti-inflammatory properties in human and experimental acute respiratory distress syndrome (ARDS). Issue 1 (December 2016) - Monaghan, Sean; Chung, Chun-Shiang; Chen, Yaping; Lomas-Neira, Joanne; Fairbrother, William; Heffernan, Daithi; Cioffi, William; Ayala, Alfred
Abstract Background Acute respiratory distress syndrome (ARDS) remains a common organ dysfunction in the critically ill patient. Mechanisms for its development have focused on immune mediated causes, aspects of our understanding are not complete, and we lack biomarkers. Design, setting, and subjects Blood and bronchial alveolar lavage fluid (BAL) from humans (n = 10–13) with ARDS and controls (n = 5–10) as well as a murine model of ARDS (n = 5–6) with controls (n = 6–7) were studied. Methods ARDS was induced in mice by hemorrhagic shock (day 1) followed by poly-microbial sepsis (day 2). Samples were then collected on the third day after the animals were euthanized. Ex vivo experiments used splenocytes from animals with ARDS cultured with and without soluble programmed death receptor-1 (sPD-1). Results Levels of sPD-1 are increased in both the serum (11, 429.3 pg/mL(SD 2133.3) vs. 8061.4(SD 4187.8), p = 0.036) and bronchial alveolar lavage (BAL) fluid (6, 311.1 pg/mL(SD 3758.0) vs. 90.7 pg/mL(SD 202.8), p = 0.002) of humans with ARDS. Similar results are seen in the serum (9396.1 pg/mL(SD 1546.0) vs. 3464.5 pg/mL(SD 2511.8), p = 0.001) and BAL fluid (2891.7 pg/mL(SD 868.1) vs. 1385.9 pg/mL(SD 927.8), p = 0.012) of mice. sPD-1 levels in murine blood (AUC = 1(1–1), p = 0.006), murine BAL fluid (AUC = 0.905(0.717–1.093), p = 0.015), and human BAL (AUC = 1(1–1), p = 0.001) fluid predicted ARDS. To assess the importance of sPD-1 in ARDS, ex vivo experiments were undertaken. BAL fluid from mice with ARDS dampens the TNF-α production compared to cells cultured with BAL lacking sPD-1 (2.7 pg/mL(SD 3.8) vs. 52.38 pg/mL(SD 25.1), p = 0.002). Conclusions This suggests sPD-1 is elevated in critical illness and may represent a potential biomarker for ARDS. In addition, sPD-1 has an anti-inflammatory mechanism in conditions of marked stress and aids in the resolution of severe inflammation. sPD-1 could be used to not only diagnose ARDS, but may be a potential therapy.